Unusual presentation of sarcoidosis, requiring a positron emission tomography/CT (PET/CT) for diagnosis - O'Riordan, Kenneth (BMJ Case Rep, 2021)
A 43-year-old man presented to hospital after routine laboratory tests showed an acute kidney injury and hypercalcaemia. He had no relevant medical history and normal physical examination, other than a 6-week history of lower back pain for which he had been taking naproxen. Low parathyroid hormone (PTH) levels indicated a PTH-independent hypercalcaemia. Investigations including CT of thorax, abdomen and pelvis and subsequent bone biopsy and renal biopsy were unremarkable. Positron emission tomography/CT (PET/CT) scan was ultimately considered as a diagnostic test and showed abnormalities in the right subpectoral and portacaval region with intense fluorodeoxyglucose F 18 uptake in local lymph nodes. A biopsy of the right subpectoral node showed granulomatous change consistent with sarcoidosis. PET/CT scanning can play an important role in the investigation of suspected malignancy, infection and inflammatory disease and in this case, was required to diagnose an atypical presentation of sarcoidosis.